Assessing Malacca wireless security implementation in government and private sector companies in – A case study - Othman, Mohd Fairuz Iskandar; Bahaman, Nazrulazhar; Muslim, Z.; Nahar, Haniza; Md Khambari, Mohd Najwan (2008)
Wireless local area networks (WLAN) have become a common technology in our everyday life. The use of WLAN can be seen among home users who use it to access the Internet and play games to business users who conduct daily business activities over the WLAN. The main objective of this case study was to ascertain the level of security with regards to wireless implementation in government and private sector companies in Malacca. To gauge the level of security being implemented, we conduct war driving sessions where we use certain hardware and software to map these wireless networks and then analyze their level of security in terms of whether they use encryption techniques such as WEP or WPA for data confidentiality. Simulation was done to show that some of these techniques are not secure. Then, comparisons are made between the use of open source software against vendor based software to collect and analyze the wireless networks before making several conclusions. The most alarming conclusion was that the level of awareness of wireless security among users in Malacca was still relatively low, especially in government sectors. Finally, we propose several steps that can be taken to minimize and counter problems faced when using wireless technology.